Cardiorespiratory motion‐compensated micro‐CT image reconstruction using an artifact model‐based motion estimation. Issue 4 (26th March 2015) - Brehm, Marcus; Sawall, Stefan; Maier, Joscha; Sauppe, Sebastian; Kachelrieß, Marc
Abstract : Purpose: Cardiac in vivo micro‐CT imaging of small animals typically requires double gating due to long scan times and high respiratory rates. The simultaneous respiratory and cardiac gating can either be done prospectively or retrospectively. In any case, for true 5D imaging, i.e., three spatial dimensions plus one respiratory‐temporal dimension plus one cardiac temporal dimension, the amount of information corresponding to a given respiratory and cardiac phase is orders of magnitude lower than the total amount of information acquired. Achieving similar image quality for 5D than for usual 3D investigations would require increasing the amount of data and thus the applied dose to the animal. Therefore, the goal is phase‐correlated imaging with high image quality but without increasing the dose level. Methods: To achieve this, the authors propose a new image reconstruction algorithm that makes use of all available projection data, also of that corresponding to other motion windows. In particular, the authors apply a motion‐compensated image reconstruction approach that sequentially compensates for respiratory and cardiac motion to decrease the impact of sparsification. In that process, all projection data are used no matter which motion phase they were acquired in. Respiratory and cardiac motion are compensated for by using motion vector fields. These motion vector fields are estimated from initial phase‐correlated reconstructions based on a deformable registration approach. To decrease the sensitivity of the registration to sparse‐view artifacts, an artifact model‐based approach is used including a cyclic consistent nonrigid registration algorithm. Results: The preliminary results indicate that the authors' approach removes the sparse‐view artifacts of conventional phase‐correlated reconstructions while maintaining temporal resolution. In addition, it achieves noise levels and spatial resolution comparable to that of nongated reconstructions due to the improved dose usage. By using the proposed motion estimation, no sensitivity to streaking artifacts has been observed. Conclusions: Using sequential double gating combined with artifact model‐based motion estimation allows to accurately estimate respiratory and cardiac motion from highly undersampled data. No sensitivity to streaking artifacts introduced by sparse angular sampling has been observed for the investigated dose levels. The motion‐compensated image reconstruction was able to correct for both, respiratory and cardiac motion, by applying the estimated motion vector fields. The administered dose per animal can thus be reduced for 5D imaging allowing for longitudinal studies at the highest image quality.